An Efficient Methodology Proposed For Deciding About the Number of Battery Modules In Hybrid Electric Vehicles. (1st January 2016) - Varesi, Kazem; Radan, Ahmad; Ghayebloo, Abbas; Nikzad, Mohammad Reza
Abstract : Selection of higher values for Degree of Hybridization (DOH) increases the fuel economy and reduces the emissions in the Hybrid Electric Vehicles (HEVs). Previously presented methodologies for deciding about the number of battery modules (as an important factor influencing the vehicle performance), presents poor vehicle performance for higher DOHs. In this paper, a new technique has been proposed for deciding about the number of battery modules in Hybrid Electric Vehicles (HEVs), by which the high performance of the vehicle is guaranteed for higher DOHs. The proposed methodology is based on satisfying two key designing factors: Maximum charge and discharge capability and satisfaction of the PNGV criteria. The proposed methodology, allows us to choose higher DOHs in HEVs, which leads to lower emissions and higher levels of fuel economy. To evaluate efficiency of proposed methodology, it has been applied on model of a test parallel passenger hybrid car available in the ADvanced VehIcle SimulatOR (ADVISOR) software. The obtained results have been compared with that of formerly presented techniques. Simulation results confirm the effectiveness of proposed methodology.